SINTESIS DAN KARAKTERISASI MEMBRAN KITOSAN SULFONAT UNTUK APLIKASI SEL BAHAN BAKAR - Velianti
Chitosan, obtained by deacetylation of chitin, is a potential biopolymer which can be used as raw material for fuel cell membranes. Chitosan has several advantages such as its hydrophilic property, good mechanical strength and easiness to be chemically modified. In order to increase the conductivity and decrease the permeability toward methanol, sulfonation of chitosan has been carried out in this work by using chlorosulfonic acid as reactant. The first method used a conventional way by dissolving the reactant in dichloromethane, while the second one was performed in a microwave oven using the same reactant in N,N-dimethylformamide . The IEC (Ion Exchange Capacity) of the resulting membranes were determined and the thermal properties were measured by TGA (Thermogravimetry Analysis). The results showed that the sulfonated chitosan membranes obtained by the conventional method had better thermal properties and higher ion exchange capacity than the ones obtained by using microwave. Unfortunately, the membranes resulted by the first method were very brittle. The SEM (Scanning Electron Microscope) photo of membrane surface confirmed that those brittle membranes had crack areas. On the other hand, the sulfonated membranes obtained by using microwave showed good mechanical properties so that they could be used further for permeation measurement. It was found that the sulfonated chitosan membranes showed a lower permeation toward methanol compared to the original chitosan membranes.